Computer model of the Grover’s algorithm - Kussainov, A.S.; Kussainov, S.G.; Turmaganbet, G.B. (Recent Contributions to Physics, 2013)
We have implemented and tested the basic steps of the computer model of the Grover’s algorithm for searching an unsorted database using Matlab software. The quantum, probabilistic algorithm of Lov Grover achieves this using O(N1/2) queries. The algorithm starts from the simulated quantum states superposition that is treated later with the Grover’s diffusion operator and its modification known as the quantum oracle, representing together the Grover’s iteration. The freedom of choice for the initial superposition of states is provided. Projection operator and measurement procedures are implemented using the basic Dirac bra-ket notation in the separate Matlab functions. The existence of an optimal time for a near-optimal measurement as a function of the number’s of the Grover’s iteration is demonstrated. Extension to the space with multiple targets is available.
Keywords: Quantum algorithm; Grover’s algorithm; oracle; computer model; Grover’s iteration